Pastoral Counseling for Congregants Experiencing Inner Wounds Caused by Toxic Leadership in the Church - Donny Charles Chandra; Sabar Parlindungan Nababan; Naftali Untung (International Journal of Christian Education and Philosophical Inquiry, 2024)
Toxic leadership in church contexts is not merely an organizational problem; it can become a psychospiritual wound when pastoral authority is used to shame, silence, manipulate, or control congregants in the name of God. This article examines pastoral counseling for congregants who experience inner wounds caused by toxic leadership in the church. The study addresses a gap in previous research: leadership studies have clarified the concepts of abusive supervision and destructive leadership. In contrast, religious trauma research has described spiritual abuse, yet fewer works have developed a constructive pastoral counseling synthesis that integrates both fields. Using a conceptual and integrative literature review design, this article draws on peer-reviewed studies on toxic leadership, spiritual abuse, institutional betrayal, moral injury, trauma-informed care, and spiritually integrated psychotherapy. The synthesis proposes that pastoral counseling in this context must be trauma-informed, spiritually competent, ecclesially accountable, and clinically humble. Three findings are advanced: toxic church leadership wounds identity, agency, and God-image; pastoral counseling must begin with safety, validation, narrative reconstruction, and protection of conscience; and recovery requires individual care and institutional repair through accountability, referral pathways, and anti-retaliatory church culture. The article concludes that pastoral counseling is most constructive when it becomes a ministry of truth-telling, non-coercive accompaniment, and communal restoration rather than a tool for preserving abusive systems.